On Counselling the Physically Disabled - Vargo, J. W. (Canadian Journal of Counselling and Psychotherapy, 2012)
It has long been recognized that people who become physically disabled typically experience certain sequential stages (denial, hostility, depression) before achieving a measure of psychological adjustment to the disability. These stages are discussed in terms of their dynamics and the counselling goals and strategies appropriate to each. To help a client overcome the handicapping effects of physical disability, a counsellor should have a rudimentary knowledge of the behavioural manifestations of the medical condition, and be skillful at implementing counselling strategies which are compatible with the intra and interpersonal dynamics characteristic of each stage.